Episodic crustal growth in the southern segment of the Trans-North China Orogen across the Archean-Proterozoic boundary - Huang, X.; Wilde, Simon; Zhong, J. (Elsevier BV, 2013)
The Dengfeng and Taihua Complexes are well-exposed Neoarchean to Paleoproterozoic units in the southern segment of the Trans-North China Orogen (TNCO). Zircon U–Pb dating shows that the Dengfeng Complex records two episodes (2568±11 Ma and 2306±6 Ma) of tonalite–trondhjemite–granodiorite (TTG) magmatism. All of the TTG rocks are characterized by high SiO2 (66.7–75.4 wt%), Na2O (3.20–5.06 wt%) and relatively low MgO (0.40–1.78 wt%). The Late Neoarchean TTG gneisses have very low contents of HREE (YbN = 0.69–2.75) and Y (1.73–7.07 ppm), with moderate [La/Yb]N (24.1–53.8) and high Sr/Y (65.1–291.3) ratios. The Early Paleoproterozoic TTG gneisses have low contents of HREE (YbN = 2.93–6.37) and Y (6.7–11.0 ppm), with moderate [La/Yb]N (10.1–27.0) and Sr/Y (10.6–52.1) ratios. Both suites show pronounced negative Nb–Ta, P and Ti anomalies but positive Sr and Pb anomalies. The Late Neoarchean TTG gneisses all have similar bulk-rock Nd and zircon Hf model ages with mainly positive eNd(t), and are interpreted as resulting from the melting of dominantly juvenile thickened lower crust with residual garnet and amphibole.The Early Paleoproterozoic TTG gneisses have extremely variable eNd(t) (-6.23 to +4.23) and heterogeneous zircon eHf(t) (-3.3 to +3.1), which are also best interpreted as resulting from the partial melting of thickened lower crust with residual amphibole and garnet. The Taihua Complex in the Xiaoqinling area records three episodes of Early Paleoproterozoic TTG magmatism (2.48 Ga at Caotan, 2.31 Ga at Houjiacun and 2.16 Ga at Bayuan), younger than the Taihua Complex in the Lushan area (2.85–2.72 Ga). All rocks have relatively low contents of HREE (YbN = 1.03–8.32) and Y (2.84–24 ppm), with moderate [La/Yb]N (8.7–88.4) and Sr/Y (19.8–125.8) ratios, and show negative Ta–Nb and Ti anomalies and positive Sr and Pb anomalies. The Caotan gneisses at 2.48 Ga and the Houjiacun TTG gneisses at 2.31 Ga have low Mg# (0.14–0.45), low Cr (>42 ppm) and Ni contents (1–21 ppm), with variable but overall positive eNd(t) and eHf(t) values, and were derived from the partial melting of thickened lower crust with residual garnet and amphibole. The younger Bayuan TTG gneisses at 2.16 Ga have low SiO2 (57.11–64.89 wt%), high MgO (2.64–4.62 wt%), Cr (100–247 ppm) and Ni (32–80 ppm), with negative whole rock eNd(t) and zircon eHf(t) values, resulted from the partial melting of delaminated lower crust that interacted with peridotitic mantle.The geochronology of the Dengfeng Complex (in the Dengfeng area) and the Taihua Complex (in the Lushan, Xiong’er and Xiaoqinling areas) reveals at least four magmatic episodes in the southern segment of the TNCO from the Late Mesoarchean to Early Paleoproterozoic (2.85–2.72 Ga, 2.57–2.48 Ga, 2.34–2.30 Ga and 2.20–2.07 Ga). The rocks of the two early episodes are dominantly of juvenile compositions with mostly positive whole rock eNd(t) and zircon eHf(t) values, suggesting two episodes of crustal growth formed in a subduction tectonic setting. The magmatic rocks of the third episode consist of both the juvenile and pre-existing crustal materials with variable whole rock eNd(t) and zircon eHf(t) values, which were generated in a subduction zone during the initial assembly of the NCC within the Columbia supercontinent cycle. The final episode of magmatism lacks juvenile materials with whole rock eNd(t) and zircon eHf(t) values being consistently negative. These may have resulted from the orogenic collapse. The episodic continental growth recorded in the southern segment of the TNCO was caused by subduction and consequent orogeny, consistent with global supercontinent cycles within the Late Archean and Early Paleoproterozoic.